2012
DOI: 10.4103/0973-1296.103648
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacokinetic comparisons of ferulic acid and puerarin after oral administration of monomer, medicinal substance aqueous extract and Nao-De-Sheng to rats

Abstract: Background:Nao-De-Sheng decoction (NDS), a traditional Chinese medicine (TCM) prescription containing Radix puerariae lobatae, Floscarthami, Radix et Rhizoma Notoginseng, Rhizoma chuanxiong and Fructus crataegi, is effective in the treatment of cerebral arteriosclerosis, ischemic cerebral stroke and apoplexy linger effect. Ferulic acid and puerarin are the main absorbed effective ingredients of NDS.Objective:To assess the affection of other components in medical material and compound recipe compatibility on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Species specificity was found in pharmacokinetics of puerarin. The pharmacokinetics of puerarin in plasma of rats and dogs coincides with the two-compartment open model (Jin & Zhu, 1992; Yang et al., 2011; Ouyang et al., 2012), while in rabbits was best fitted to the three-compartment open model (Jin & Zhu, 1992).…”
Section: Pharmacokinetics Of Puerarinmentioning
confidence: 70%
“…Species specificity was found in pharmacokinetics of puerarin. The pharmacokinetics of puerarin in plasma of rats and dogs coincides with the two-compartment open model (Jin & Zhu, 1992; Yang et al., 2011; Ouyang et al., 2012), while in rabbits was best fitted to the three-compartment open model (Jin & Zhu, 1992).…”
Section: Pharmacokinetics Of Puerarinmentioning
confidence: 70%
“…Several pharmacokinetic and tissue distribution studies focus on normal animal,[ 14 ] regardless of pathological condition. Our study showed that blood stasis was associated with significantly higher AUC, C max , t 1/2 and lower CL and Vd of tanshinone IIA in plasma and higher AUC 0-t of tanshinone IIA in the analyzed tissues of rats treated with BHQ.…”
Section: Resultsmentioning
confidence: 99%
“…Ischemic stroke has a very acute onset, and if not treated immediately, it often leads to severe disability or death. This disease occurs commonly in elderly patients, in whose morbidity and mortality rates rank first among neurological diseases ( 12 ). Ischemic stroke is mainly due to cerebral arterial atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%